2020
DOI: 10.3233/jpd-202138
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 and the Endolysosomal System in Parkinson’s Disease

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) cause autosomal dominant familial Parkinson’s disease (PD), with pathogenic mutations enhancing LRRK2 kinase activity. There is a growing body of evidence indicating that LRRK2 contributes to neuronal damage and pathology both in familial and sporadic PD, making it of particular interest for understanding the molecular pathways that underlie PD. Although LRRK2 has been extensively studied to date, our understanding of the seemingly diverse functions of LRRK2 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 176 publications
(352 reference statements)
0
59
0
Order By: Relevance
“…The endosomal pathway starts with clathrin-mediated endocytosis and vesicle uncoating, followed by fusion with early endosomes [ 39 ]. These early endosomes facilitate the uncoupling of ligands and membrane-bound receptors for recycling, while playing a role as a sorting station, directing cargo towards multiple destinations: (i) directly to the cell surface through recycling endosomes, (ii) to the lysosomes through maturation-mediated by endosomal sorting complexes required for transport (ESCRT) directed for degradation or (iii) to the trans -Golgi network (TGN) for retrograde sorting ( Figure 1 A) [ 39 ].…”
Section: The Endolysosomal System Is Impaired In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The endosomal pathway starts with clathrin-mediated endocytosis and vesicle uncoating, followed by fusion with early endosomes [ 39 ]. These early endosomes facilitate the uncoupling of ligands and membrane-bound receptors for recycling, while playing a role as a sorting station, directing cargo towards multiple destinations: (i) directly to the cell surface through recycling endosomes, (ii) to the lysosomes through maturation-mediated by endosomal sorting complexes required for transport (ESCRT) directed for degradation or (iii) to the trans -Golgi network (TGN) for retrograde sorting ( Figure 1 A) [ 39 ].…”
Section: The Endolysosomal System Is Impaired In Parkinson’s Diseasementioning
confidence: 99%
“…The endosomal pathway starts with clathrin-mediated endocytosis and vesicle uncoating, followed by fusion with early endosomes [ 39 ]. These early endosomes facilitate the uncoupling of ligands and membrane-bound receptors for recycling, while playing a role as a sorting station, directing cargo towards multiple destinations: (i) directly to the cell surface through recycling endosomes, (ii) to the lysosomes through maturation-mediated by endosomal sorting complexes required for transport (ESCRT) directed for degradation or (iii) to the trans -Golgi network (TGN) for retrograde sorting ( Figure 1 A) [ 39 ]. The key regulators of these pathways are the Rab GTPases (Rabs) proteins, which are implicated in maintaining specific interactions with other effector proteins such as coat proteins (clathrin-AP1, COPI, and AP3), motor proteins (Dynein-Dynactin, KIF5B, KIF1A, and KIF13A), and tethering complexes such as EEA-1 and SNAREs proteins ( Figure 1 B) [ 40 , 41 , 42 ].…”
Section: The Endolysosomal System Is Impaired In Parkinson’s Diseasementioning
confidence: 99%
“…C. elegans functional studies of other Mendelian PD genes and their orthologues, including PINK1, PARKIN, ATP13A2 and DJ-1 , or PD risk genes, such as GBA1 , have proven the strength of this invertebrate model, highlighting highly conserved functions of these genes and proteins in cellular pathways disrupted in PD, including mitophagy, lysosomal degradation and α-synuclein pathology [ 49 , 132 , 175 , 262–270 ]. Complex functional interaction of all of these PD proteins and LRRK2 have been described in PD patient samples and in animal models, which supports the idea that LRRK2 is a master regulator of cellular trafficking and quality control pathways, maintaining a cross-talk of a multitude of cellular processes and reflects on the high complexity of Parkinson’s disease pathology [ 13 , 271–274 ]. Developing oligogenic C. elegans models, replicating the human genetic changes and evaluating cross-talk of various cellular pathways in PD, will help in enabling the future development of novel, disease modifying therapeutics.…”
Section: Lrrk2 and Beyond: The Potential Of C Elegans For Functional Modelling Of Parkinson’s Disease Gwas Candidate Gmentioning
confidence: 65%
“…In the development of PD, the regulation of autophagy is essential ( Zhu et al, 2019 ; Wan et al, 2020 ). The damage to the autophagy pathway and the resulting accumulation of misfolded α-synuclein and other proteins aggregates represent the common pathobiological characteristics of neurodegenerative diseases such as PD ( Erb and Moore, 2020 ; Kwon et al, 2020 ). A previous study showed that neurons need autophagy for catabolism to mediate the replacement of damaged organelles and promote synaptic remodeling, thus, autophagy impairment can lead to PD ( Moors et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%